Money, Finance, and the Political Economy of Development in Ghana - Akolgo, Isaac Abotebuno (2025)
This cumulative dissertation is both a study of development financing in post-independence Ghana and a response to recent International Political Economy(IPE) debates on the nature and operation of finance capitalism within countries and globally. My main argument is that since political independence in 1957, Ghana’s attempts for economic transformation have been primarily frustrated by a finance constraint. A financial constraint is used here to capture not only an insufficiency or mismanagement of development finance, but also the constrictive, anti-developmental, and exploitative tendencies of global and domestic finance, the financial system, and financial policy. In the three articles that constitute this dissertation, I demonstrate the financial constraint to Ghana’s development by responding to ongoing IPE debates that suggest that there has been a dysfunction of finance within the global capitalist system. This dysfunction, it has been argued, is that finance either has failed to support the real productive sector or has expanded disproportionately beyond the productive economy, domestically and globally. Particularly for countries in the global South, this dysfunction in finance has impeded their economic transformation. Methodologically, I employ a mix of quantitative and qualitative analyses across the three articles, drawing micro and macro level data from several sources including the Bank of Ghana, World Bank, IMF, the Ministry of Finance of Ghana, and primary data from interviews on the use of mobile money in Ghana. In the first article: Ghana’s debt crisis and the political economy of financial dependence: history repeating itself? I show a macro level dysfunction in finance that resulted in Ghana’s 2022-2023 sovereign debt crisis. I place the country’s public debt statistics in historical and political context, arguing that its fall into a debt crisis is a consequence of a weak and dependent economic structure inherited from colonialism and perpetuated by liberal economic policies; the exploitative transnational lending system under which it procures external debt; and recent government policy errors. In the second article, On the contradictions of Africa’s fintech boom: evidence from Ghana, I show a micro level dysfunction in finance under which the rollout of mobile money to promote financial inclusion faces the challenges of regressive taxation, exorbitant transaction costs, and customer indebtedness from digital microloans. In the third article, Banking and monetary policy in Ghana: has finance served the real economy? I show both a macro and micro level dysfunction in finance and financial policy under which commercial banks’ lending to the agricultural and manufacturing sector has significantly declined between 1999 and 2023. Collectively, I demonstrate that these various dysfunctions in finance have impeded Ghana’s development. On the basis of this, I make recommendations for reforms of Ghanaian financial and economic policy under each paper.
Keywords: Ghana; Financial System; Debt; Monetary Policy; Financial Technology; Africa